Exploring community-based reporting of livestock abortions for Rift Valley fever and brucellosis surveillance in Uganda: a pilot study - Walekhwa, A.W.; Conlan, A.J.K.; Atim, S.A.; Ademun, A.R.; Hasahya, Emmanuel; Wood, J.L.N.; Mugisha, L. (Nature Research, 2025)
Rift Valley fever (RVF) and brucellosis are serious zoonotic diseases with significant public health and economic consequences. In livestock, both diseases are associated with abortions that are not routinely reported as part of disease surveillance. We piloted a community-driven call centre initiative in Isingiro District, Uganda, from March to June 2023, aimed at facilitating the reporting of livestock abortions. The community call centre was promoted through stakeholder engagements, social media campaigns, and targeted sensitisation materials.